Printed electronic devices and systems for interfacing with single cells up to organoids - Saghafi, Mahsa K.; Vasantham, Srivatsan K.; Hussain, Navid; Mathew, George; Colombo, Federico; Schamberger, Barbara; Pohl, Eric; Cadilha Marques, Gabriel; Breitung, Ben; Tanaka, Motomu; Bastmeyer, Martin; Selhuber-Unkel, Christine; et al. (Advanced functional materials, 2023)
The field of bioelectronics with the aim to contact cells, cell clusters, biological tissues and organoids has become a vast enterprise. Currently, it is mainly relying on classical micro- and nanofabrication methods to build devices and systems. Very recently the field is highly pushed by the development of novel printable organic, inorganic and biomaterials as well as advanced digital printing technologies such as laser and inkjet printing employed in this endeavor. Recent advantages in alternative additive manufacturing and 3D printing methods enable interesting new routes, in particular for applications requiring the incorporation of delicate biomaterials or creation of 3D scaffold structures that show a high potential for bioelectronics and building of hybrid bio-/inorganic devices. Here the current state of printed 2D and 3D electronic structures and related lithography techniques for the interfacing of electronic devices with biological systems are reviewed. The focus lies on in vitro applications for interfacing single cell, cell clusters, and organoids. Challenges and future prospects are discussed for all-printed hybrid bio/electronic systems targeting biomedical research, diagnostics, and health monitoring.
Gesehen am 27.05.2024